Strain-life estimation of the last stage blade in steam turbine during low volume flow conditions. (July 2021) - Cao, Lihua; Xu, Meichao; Luo, Huanhuan; Si, Heyong
Highlights: The strain-life of the last stage under low volume flow conditions is predicted. Two-way FSI method is adopted to calculate the strain range. The strain-life is affected by the excitation of the rotor-stator clearance vortex. The strain-life of 90% span of blade suction surface is the shortest. The strain-life of blade decrease with the decrease of volume flow. Abstract: Based on the elastic-plastic analysis, the local strain-life of the last stage of steam turbine under the low volume flow conditions is predicted. Considering the unsteady flow steam force and local high temperature of blade, the three-dimensional transient flow field, strain distribution and stress distribution of the last stage blade are calculated by the two-way fluid structure interaction method. Under low volume flow conditions, the temperature of blade tip increases with the decrease of volume flow. In addition, the self-excited unsteady frequency of rotor -stator clearance vortex is obtained at 90% span. According to the distribution of maximum equivalent stress on the rotor blade surface, three dangerous points are identified, which are located at the blade tip of the pressure surface (DP1), 90% span of the suction surface (DP2) and the trailing edge at the blade root of the pressure surface (DP3). With the decrease of volume flow, the equivalent stress and strain range of dangerous points increase, so the strain- life of dangerous points decreases. Among them, the strain-life of DP2 is the shortest at case3 condition. The strain response frequency of DP2 is consistent with the self-excited unsteady frequency of rotor -stator clearance vortex, which proves that it is necessary to consider the unsteady steam flow force in strain-life calculation. This study provides theoretical guidance for the safe operation time of the steam turbine under low volume flow conditions.